Efforts To Harmonize Conflicts In The Regulation Of Corporate Social Responsibility (Csr) In The Indonesian Legal System - Basrawi Basrawi; Laode Awal Sakti; Jusafri Jusafri; Putri Aulia; Satmawati Satmawati (Universitas Negeri Semarang, 2025)
The focus of this research is on the critical issue of overlapping Corporate Social Responsibility (CSR) regulations within Indonesia's legal system. This is a significant problem that affects business compliance and social development outcomes. The study investigates the normative juridical aspects of various legislative frameworks, including the Company Law, Investment Law, and Mining Law. The study identifies three major consequences of regulatory redundancy: uncertainty in implementation standards, resource inefficiency due to program duplication, and complexity in supervision. It highlights systemic weaknesses within Indonesia's CSR legislative system and proposes an innovative legislative model to integrate CSR. To enhance legal certainty and implementation effectiveness, the study recommends a comprehensive harmonization method that integrates regulations, establishes consistent implementation mechanisms, and develops supervision protocols. These findings assist policymakers and legal practitioners in improving Indonesia's CSR regulatory framework.